Organisational Challenges to Corporate Social Responsibility - Deus, Rafael Mattos [UNESP] (2019)
Corporate social responsibility (CSR) is part of the sustainability debate within organizations and, consequently, a number of systems to manage this issue have emerged. ISO 26000, for example, aims to assist organizations in contributing to sustainable development and employing international standards of behaviour. This type of standard is attractive, but there are some challenges that organizations need to face before adopting it. Considering these challenges, this chapter presents some characteristics of ISO 26000 and the main drivers and barriers to adopting CSR initiatives as well social standards. The literature is investigated to present important findings about CSR, social standards, and the drivers and barriers of CSR. The chapter presents in detail the main drivers toward CSR, e.g., stakeholder pressure, globalization, reputation, competitive advantage, decrease in risks around the business, government laws, improving the relationship between employees and the organization, improving the relationship between co-workers, compatibility with other standards, and company size. Just as there are drivers, there are also barriers to ISO implementation. The chapter also presents some of the barriers to the implementation of CSR systems and standards, e.g., lack of knowledge or awareness of CSR, lack of knowledge about how to implement CSR with the organization’s strategy, commercial barriers (national and international), lack of sensitivity to the theme, and financial resources. The barriers can be a challenge for organizational management. Organizations can use the tools presented by the standards and take advantage of the drivers, reinforcing their convictions and justifying their actions in order to implement CSR initiatives.